2017
DOI: 10.1093/ofid/ofx163.644
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Carbapenem-Resistant Enterobacteriaceae Infections with Ceftazidime-Avibactam

Abstract: BackgroundCRE is an urgent threats to public health with a high mortality estimated at >30–50%. Until recently, polymyxin-based antibiotics were the only available options. However, a new therapeutic option has become available: ceftazidime-avibactam. We sought to describe outcomes from these infections treated with ceftazidime-avibactam.MethodsFrom 9/2015 to 12/ 2016, we reviewed charts of 11 patients infected with CRE who received ceftazidime-avibactam at USC (Los Angeles, CA). Sixteen isolates analyzed. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Recurrence occurred in two patients (18%). Decreased sensitivity to ceftazidime-avibactam was noted in one patient (9%), and three patients (27%) had CRE isolated after C 7 days of treatment [39]. In the cohort of six patients, five achieved clinical cure; however, two relapsed with the same KPC-3producing K. pneumoniae strain within 3 weeks of completing ceftazidime-avibactam treatment [38].…”
Section: Retrospective Cohort/chart Review Studiesmentioning
confidence: 97%
See 4 more Smart Citations
“…Recurrence occurred in two patients (18%). Decreased sensitivity to ceftazidime-avibactam was noted in one patient (9%), and three patients (27%) had CRE isolated after C 7 days of treatment [39]. In the cohort of six patients, five achieved clinical cure; however, two relapsed with the same KPC-3producing K. pneumoniae strain within 3 weeks of completing ceftazidime-avibactam treatment [38].…”
Section: Retrospective Cohort/chart Review Studiesmentioning
confidence: 97%
“…Data for 1155 patients treated with ceftazidimeavibactam from 16 retrospective non-comparative cohort/chart review studies were identified (Table 3) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], the majority of which involved CRE/CPE infections (981 patients); six publications included data for P. aeruginosa infections (124 patients). Emergence of resistance and/or reduced susceptibility to ceftazidime-avibactam was reported in seven of these publications, including one OXA-48-producing K. pneumoniae in a single patient [35]; in the remaining cases, the resistant strains were either K. pneumoniae carbapenemase (KPC)-producing K. pneumoniae or carbapenem-resistant K. pneumoniae (CRKP) with unreported resistance mechanisms [32-35, 46, 47].…”
Section: Retrospective Cohort/chart Review Studiesmentioning
confidence: 99%
See 3 more Smart Citations